Silent victims or agents of change? An exploration of the lived experiences of African widows confronted with the practice of customary law of succession and inheritance in South Africa - Ndlovu, Thatshisiwe (My University, 2016)
This study seeks to explore the lived experiences of black South African widows living in a poor socio-economic locality using a qualitative research design, which allows for deeper engagement of widows’ experiences of their own world. Having benefited immensely from reviewing literature on numerous legislative measures that have been enacted to protect the rights of women in South Africa, this study takes an entry point of analysing experiences of widowhood from the widow’s perspective. Underpinned by the central question of examining how and in what ways customary practices of inheritance have affected the lived experiences of widows, the study challenges the view that African widows are silent and helpless victims of patriarchal beliefs and practices. It presents findings drawn from life history narratives of ten black women living in low-socio economic areas of Midrand and Tembisa located in the present day Gauteng province of South Africa, which indicated that widows in this locality were victims of structural, political and socio-economic factors. It also observed that widows were also victims of invisible and often unrecognised power of patriarchal attitudes that have lingered on. The study then deployed a feminist narrative approach to analyse the findings, which shows that some of the black women’s experiences are informed by their socio-cultural realities and their lives are shaped by the unique intersection between race, gender and social class. Drawing from the main findings, I argue that culture, patriarchy, tradition, gender, and class are not distinct realms of experience, existing in isolation; rather they come into existence in and through relations with each other. Furthermore, the study argues that the connection between widowhood and law is marked by contradictions and uncertainties, which are deeply embedded in unequal power relations, socio-cultural and legislative measures of the broader post-apartheid South African context. By extension, this has seen such dynamics as class, level of education and types of marriages strongly playing themselves out in the lived experiences of widowhood. The study uses this as a launch pad to argue that in various ways, African widows exercise their agency, their silence being one of their chosen forms of resistance to challenge and question patriarchal domination. This study then suggests that widows and the experience of widowhood ought not to be seen from a homogenizing approach, as it tends to mask the limitations of legislative measures as an effective mechanism in countering the negative effects of customary and traditional practices.
A research report submitted to the Faculty of Humanities in partial fulfilment of the requirements of the Masters of Arts degree in Development Studies. University of the Witwatersrand Johannesburg March 2015